Enzymatic properties and applications of the inulin fructotransferase from Nocardiaceae family - Cheng, Yuanyuan (fi=Turun yliopisto|en=University of Turku|, 2018)
Difructose anhydride I (α-D-fructofuranose-2′, 1:2, 1′-β-D-fructofuranose dianhydride, DFA I) is an annular disaccharide consisting of two fructose units. DFA I and functional disaccharides, difructose anhydride III (α-D-fructofuranose-2’, 1:2, 3’-β-D-fructofuranose dianhydride, DFA III) are isomers. In this thesis, three recombined inulin fructotransferase (IFTase) from Nocardiaceae family: Nocardioides luteus (NoluIFTase), Nocardioides sp. JS614 (NospIFTase) and Nocardioides bacterium Broad-1 (NobaIFTase) were synthesized and their enzymatic properties studied. Novel method to produce DFA I was designed. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) showed that the monomer molecular mass of three enzymes ranged from 41,000 to 42,000 Da, their whole molecular mass was detected to be ranged from 50,000 to 62,000 Da by gel column, the two results showed that three enzymes were monomers. The enzymatic properties of three recombinant enzymes were investigated by high performance liquid chromatography (HPLC). They had similar optimum pH and temperature. NospIFTase had the best thermal stability and it had the highest conversion ratio of inulin to DFA I. The smallest substrate was determined as nystose GF3. Optimum pH was determined to be 6.0 for double-enzymes coupled reaction and inulosucrase originated from Lactobacillus gasseri DSM 20604 showed max activity of transferring sucrose into inulin at 45°C. At present, no DFA I-forming IFTases from Nocardiaceae has been reported. The conclusion of this paper is of great significance for expanding the research scope of DFA I IFTase. The double enzyme method provides a new way for the synthesis of DFA I and reduces the cost of DFA I synthesis.